2022
DOI: 10.1186/s12974-022-02652-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional distinctions of co-resident microglia and monocyte-derived macrophages after retinal degeneration

Abstract: Background Both resident microglia and invading peripheral immune cells can respond to injury and degeneration in the central nervous system. However, after dead and dying neurons have been cleared and homeostasis is re-established, it is unknown whether resident immune cells fully resume normal functions and to what degree the peripheral immune cells take up residence. Methods Using flow cytometry, in vivo retinal imaging, immunohistochemistry, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…(82) Intriguingly, macrophages also increased the expression of microglial core genes during the acute SIV infection. In a different system, it was found that the monocyte-derived macrophages in the retina adopted microglia-like gene expression during the degeneration processes, (83) which was similar to what we found for the CAMs in acute SIV infection. However, the reasons why CAMs share more similarities with microglia in response to stress or neurodegenerative diseases are still unknown.…”
Section: Discussionsupporting
confidence: 85%
“…(82) Intriguingly, macrophages also increased the expression of microglial core genes during the acute SIV infection. In a different system, it was found that the monocyte-derived macrophages in the retina adopted microglia-like gene expression during the degeneration processes, (83) which was similar to what we found for the CAMs in acute SIV infection. However, the reasons why CAMs share more similarities with microglia in response to stress or neurodegenerative diseases are still unknown.…”
Section: Discussionsupporting
confidence: 85%
“… 16 Monocyte-derived macrophages infiltrating the retina can differentiate into microglia-like cells but are distinct from resident microglia. 17 , 18 These monocyte-derived macrophages can remain in the retina for extended periods, adopting a microglia-like morphology and gene expression profile, although they exhibit differences in gene expression, such as class II major histocompatibility complex (MHCII) levels. 17 , 18 The infiltration of monocyte-derived macrophages into the retina is part of the immune response to degeneration, and their presence can be crucial in disease states affecting the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Despite observing an increase in the number of Ly6C hi monocytes within the bone marrow of Akita mice, we noted that the number of proinflammatory monocytes derived from the bone marrow in the retina remained unchanged. One plausible interpretation of this observation is that upon migration into the retina, a considerable fraction of these monocytes undergo differentiation into macrophages [40]. These macrophages, in turn, intensify the inflammatory response by releasing an array of cytokines and other inflammatory molecules.…”
Section: Discussionmentioning
confidence: 99%